Dampak Pengetahuan, Kesadaran, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Kendaraan di Medan - Hantono Hantono; Selvia Fransiska Wijaya (Owner : Riset dan Jurnal Akuntansi, 2025)
Taxpayer compliance is a crucial factor that determines the success of the taxation system in a region. However, in Medan City, the level of motor vehicle taxpayer compliance remains relatively low. This can be observed from the low tax payment rates and high levels of motor vehicle tax arrears. One of the contributing factors is the lack of public understanding about the importance of taxes and the applicable tax mechanisms. Additionally, taxpayer awareness and the suboptimal accountability of public services also affect tax compliance. Therefore, there is a need for research to better understand the factors influencing motor vehicle taxpayer compliance in Medan City. This study aims to analyze the influence of tax knowledge, taxpayer awareness, public service accountability, and tax sanctions on the compliance of motor vehicle taxpayers in Medan City..